Effect of Charred Biomass addition on Fertility Characteristics of Soil - Shayanthan, A.; Gnanavelrajah, N. (South eastern of Sri lanka, 2012)
Charred biomass (CB) could be used to enhance agricultural productivity by improving soil quality. A laboratory incubation study was conducted to find out the effect of application of CB alone and in combination with inorganic fertilizers on selected properties of Chemmani series of Jaffna peninsula. Treatments were T0 (control), T1 (CB), T2 (NPK fertilizer), and T3 (combination). Complete randomized design was used with three replicates. Results of incubation experiment indicated that pH of soil significantly increased in T1 (CB) and decreased in T2 (NPK fertilizer). pH was significantly low in T3 (combination) compared to control. EC was significantly increased in NPK fertilizer followed by T3 (combination) and T1 (CB) compared to control. Available N was significantly higher in T3 (combination) and T2 (NPK fertilizers) compared to T0. Available P was significantly increased in T2 (NPK fertilizer) followed by and T3 (combination) compared to T1 (CB) and T0. Available K was significantly increased in T1 (CB) and T3 (combination) compared to T2 (NPK fertilizer) and control. Cation exchange capacity and microbial biomass carbon were significantly increased with T1 (CB) followed by T3 (combination) compared to other treatments. Results indicate that though CB alone has a negative effect on soil pH during initial stage, CB has potential to enhance the soil fertility parameters compared to T2 (NPK fertilizer) and control. Combination of CB and inorganic fertilizers shows significant favorable effects on fertility compared to other treatments.
Keywords: Charred biomass; Available nutrients; Microbial biomass; Cation exchange capacity.